PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP HASIL BELAJAR MENGGAMBAR MODEL SISWA KELAS VIII SMP NEGERI 1 SAWAHLUNTO - Mella Darmayanti; Ramalis Hakim (Serupa The Journal of Art Education, 2020)
The background in this study is based on the low completeness od student learning outcomers because the models and the methods taught by the teacher in the learning are less effective. This is influenced by educators who usually use old methods such as the lecture methods rather than participation and guidance so that teachers or educator play a more expert role in taching which make students less active during learning. The problems solving to outcome it is by applying a project based learning model. This study aims to determine the learning outcomes od students using the PJBL model (project based learning) with the learning outcomes of studenst using picture and picture at State of Junior High School 1 Sawahlunto. The population on this study were 142 students from grade 8 in the academci year 2020/2021. The sampling using random sampling obtainde from the experimental class (VIII2) totaling 28 students and from the control class (VIII3) totally 28 students. This research using a Normality test, homogenity test and hypothesis test were applied using SPSS 16. The results of this study obtainde the average of the experimental class, namely 83.39 and 81.64 for the control class. In this research, hypothesis testing is used: if t-count>t-table the Ho is rejected. And Ha is accepted. After testing the one way hypothesis, it is obtained t-count<t-table (0.941<2.004), ho Ho is Accepted and Ha is Rejected. So teh learning outcomes using a project based learning are no differennt with teh picture and picture in state of junior high school 1 Sawahlunto.Keywords :Student Learning Outcomes, Project-based learning models, picture and picture models.